PENGGUNAAN ARBITRAGE PRICING THEORY DALAM MENGUKUR RETURN KELOMPOK SAHAM SEKTORAL - I Gede Widya Anantayoga; Noer Azam Achsani; Tubagus Nur Ahmad Maulana (Pusbindiklat - LIPI, 2014)
There are some approaches that can be done to quantify the risk for investors in order to produce maximum yields and one of the models used is the Arbitrage Pricing Theory (APT). APT is considered more flexible than the Capital Asset Pricing Model (CAPM) because the model can use a variety of various macroeconomic factors in calculating the risk premium of an asset or to establish a model of asset valuation. Macroeconomic factors of an established model can change over time so does the risk premium contained. The purpose of this study is to do analysis using APT whether macroeconomic variables (oil prices, the exchange rate of IDR against the USD, and the rate of inflation) are factors that affected stock returns in sectoral index in Indonesia. This study uses the time span from January 2007 to December 2012 with the object of study is 9 different sectors in sectoral stocks indice, whereas the method used is multiple linear regression. This study concludes that among the three macroeconomic factor that are used as research material (crude oil prices, the exchange rate of the rupiah against the U.S. dollar, and inflation), the dollar exchange rate is the most significant factors in measuring the sensitivity of return of sectoral stocks indice.